2005
DOI: 10.1007/s00285-005-0339-1
|View full text |Cite
|
Sign up to set email alerts
|

A delay recruitment model of the cardiovascular control system

Abstract: We develop a nonlinear delay-differential equation for the human cardiovascular control system, and use it to explore blood pressure and heart rate variability under short-term baroreflex control. The model incorporates an intrinsically stable heart rate in the absence of nervous control, and allows us to compare the baroreflex influence on heart rate and peripheral resistance. Analytical simplifications of the model allow a general investigation of the rôles played by gain and delay, and the effects of ageing. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Research has shown that baroreflex control of resting BP occurs via modulation of sympathetic and parasympathetic nerve activity supplying the heart, and sympathetic innervation of the peripheral vasculature (Eckberg et al 1972;O'Leary and Seamans 1993;Fowler and McGuinness 2005). It was hypothesized that since MAP increases significantly during isometric exercise, repeated exposures to this pressor response may serve as a stimulus for baroreceptor resetting (Wiley et al 1992), presumably to a lower operating point (O'Leary 1996).…”
Section: General Overview Of Findingsmentioning
confidence: 99%
“…Research has shown that baroreflex control of resting BP occurs via modulation of sympathetic and parasympathetic nerve activity supplying the heart, and sympathetic innervation of the peripheral vasculature (Eckberg et al 1972;O'Leary and Seamans 1993;Fowler and McGuinness 2005). It was hypothesized that since MAP increases significantly during isometric exercise, repeated exposures to this pressor response may serve as a stimulus for baroreceptor resetting (Wiley et al 1992), presumably to a lower operating point (O'Leary 1996).…”
Section: General Overview Of Findingsmentioning
confidence: 99%
“…The heart and pulmonary system are effectively combined into one cardiac output term. We assume (i) a closed system with incompressible blood, thereby conserving blood volume, (ii) compliant arteries and veins, and (iii) the capillary system is like a resistance vessel [15].…”
Section: The Modelmentioning
confidence: 99%
“…The Hill function g(p) represents the pressuredependent baroreceptor control. The default values used by Fowler and McGuinness [15] were α = 1.3, β = 0.3, ε h = 0.18, ε p = 0.3, ν = 0.4, δ = 1, µ = 0.5, γ = 0.2, n = 3. The influence of respiration is controlled by the amplitudes A 1 and A 2 (dimensionless), frequency f r (s −1 ), and phase lag φ (dimensionless) of the response; we take φ = π.…”
Section: The Modelmentioning
confidence: 99%
“…This process is described in [1]. Mathematical modeling of this process leads to a system of differential equations with delay.…”
mentioning
confidence: 99%